KAJIAN YURIDIS KEDUDUKAN MAHKAMAH KONSTITUSI SEBAGAI POSITIF LEGISLATOR MELALUI MEKANISME JUDICIAL REVIEW - NIM. A1011181056, YUSTINA VENERANDA NOVI (Jurnal Fatwa Hukum, 2022)
AbstractThe Constitutional Court is one of the implementations of judicial power in Indonesia. The authority attached to the Constitutional Court can be seen in Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia (UUD NRI Tahun 1945). Testing the Law or what is commonly called Judicial Review is one of them, as part of the check and balance process. In terms of testing the law, the Constitutional Court uses the 1945 Constitution as its "touchstone". The decision of the Constitutional Court that examines the Law certainly has a close relationship with the norms contained in the petitioned for review. Rules are basically the product of the legislature. To avoid overlap between legislative institutions, the term Positive Legislator is known, which is an inherent characteristic of institutions that can form rules, namely the legislature (but in the formation process, Law No. 12 of 2011 concerning the Formation of Legislation provides space for the executive, the president to be involved and determine). There is also the term Negative Legislator, which is a characteristic attached to an institution to be able to cancel the norms contained in a rule. The Constitutional Court through its decisions is a Negative Legislator. However, in some of its decisions, the Constitutional Court is actually present as a Positive Legislator, which can also be seen juridically in the inconsistency of the Constitutional Court in terms of restrictions that should be applied in its decisions. So the title of this research is "Juridical Study of the Position of the Constitutional Court as a Positive Legislator through the Judicial Review Mechanism". The problem formulations of this research are: "How is the position of the Constitutional Court as a Positive Legislator through the Judicial Review mechanism on the existence of legislative and executive institutions in the state system in Indonesia?" and "How is the reconstruction that needs to be done in terms of the authority of the Judicial Review by the Constitutional Court in Indonesia?". This research was conducted with the aim of knowing and analyzing the position of the Constitutional Court in the state system as one of the judicial power institutions through the Judicial Review mechanism and then developing into a Positive Legislator, and whether or not a reconstruction needs to be carried out. The method the author uses is normative legal research conducted by examining library materials or secondary data, namely examining laws and regulations that apply or are applied to a particular legal problem.Keywords: Constitutional Court, Judicial Review, Positive Legislator, Negative Legislator Abstrak Mahkamah Konstitusi adalah satu di antara pelaksanaan kekuasaan kehakiman yang ada di negara Indonesia. Kewenangan yang dilekatkan pada Mahkamah Konstitusi bisa dilihat pada pasal 24C ayat (1) Undang Undang Dasar Negara Republik Indonesia Tahun 1945 (UUD NRI Tahun 1945). Pengujian Undang-Undang atau yang biasa disebut Judicial Review adalah satu di antaranya, sebagai bagian dari proses check and balance. Dalam hal pengujian Undang-Undang, Mahkamah Konstitusi menggunakan UUD NRI Tahun 1945 sebagai "batu uji"-nya. Putusan Mahkamah Konstitusi yang menguji Undang-Undang tentu memiliki kaitan erat dengan norma yang tertuang dalam yang dimohonkan untuk diuji. Aturan pada dasarnya merupakan produk dari lembaga legislatif. Untuk menghindari terjadinya over-lap antara lembaga legislatif maka kemudian dikenal adanya istilah Positif Legislator, yakni sifat yang melekat pada lembaga yang dapat membentuk aturan, yakni lembaga legislatif (namun dalam proses pembentukannya, UU No. 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan menyediakan ruang untuk eksekutif, presiden untuk terlibat dan menentukan). Ada pula istilah Negatif Legislator, yakni sifat yang dilekatkan pada suatu lembaga untuk dapat membatalkan norma yang terdapat dalam suatu aturan. Mahkamah Konstitusi melalui putusannya adalah sebagai Negatif Legislator. Namun dalam beberapa putusannya, Mahkamah Konstitusi justru hadir sebagai Positif Legislator yang juga secara yuridis bisa dilihat pada ketidakkonsistenan Mahkamah Konstitusi dalam hal pembatasan yang seharusnya diterapkan dalam putusannya. Maka judul dari penelitian ini adalah "Kajian Yuridis Kedudukan Mahkamah Konstitusi sebagai Positif Legislator Melalui Mekanisme Judicial Review". Adapun rumusan masalah dari penelitian ini adalah : "Bagaimana kedudukan Mahkamah Konstitusi sebagai Positif Legislator melalui mekanisme Judicial Review terhadap keberadaan lembaga legislatif dan eksekutif dalam sistem ketatanegaraan di Indonesia?" dan "Bagaimana rekonstruksi yang perlu dilakukan dalam hal kewenangan Judicial Review oleh Mahkamah Konstitusi di Indonesia?". Penelitian ini dilakukan dengan tujuan untuk mengetahui dan menganalisis kedudukan Mahkamah Konstitusi dalam sistem ketatanegaraan sebagai sebagai satu di antara lembaga kekuasaan kehakiman melalui mekanisme Judicial Review kemudian berkembang menjadi Positif Legislator, serta perlu atau tidakkah sebuah rekonstruksi dilakukan. Metode yang penulis gunakan adalah penelitian hukum normatif yang dilakukan dengan cara meneliti bahan pustaka atau data sekunder, yakni mengkaji peraturan perundang-undangan yang berlaku atau diterapkan terhadap suatu permasalahan hukum tertentu.Kata Kunci : Mahkamah Konstitusi, Judicial Review, Positif Legislator, Negatif Legislator